MENYONGSONG PERGESERAN PERAN PROFESI AKUNTAN MANAJEMEN DALAM ERA TEKNOLOGI INFORMASI - Mulyadi (UGM, 2000)
Canadian management accountants have shifed their roles accounting staff whose functions are generating routine accounting information and report to a position as senior member of management team whose jobs are making strategic decisions. They also changed the knowlodge used as a basis for their professional competence from traditional cost accounting to advanced management control process. In the information technology era, companies need professionals who have competence in designing, installing and operating management control system which can be used to multiply companies performances. Indonesian management accounting profession needs to shift its role, susch as that has been dones by Canadian management accounting profession. The shify is a respond to the more intensive and extensive use of information technology in the process of providing customer value. The shift has a great impact on the education of students who want to enter management accounting profession and new skills needed by management accountant practitioners. This paper discussed the shifting role of management accountants in the information technology era and its impact on the knowledge used as a new basis of professional competence of management accounting profession. In this paper, I analyzed the scope and modernity of the content of several books on management control system, for providing information to lectures in choosing an appropriate textbook for building the new basis of management accountant professional competence.